Evaluation of a Filament-Winding Composite and Aluminium 6061 Frame for Electric Vehicles - Yunus Bakhtiar Arafat; Muhamad Fahmi As'ari; Rachmat Anggi Marvianto; Muhamad Hananuputra Setianto; Wahyu Sulistiyo (International Journal of Engineering Continuity, 2025)
This study evaluates the structural performance of electric motorcycle frames made of 6061 aluminium alloy and filament winding-based composites using the Finite Element Method (FEM) approach. The main objective of this study is to compare the deformation response, stress distribution, and safety factors of both materials in the same frame geometry and loading conditions, so that the influence of material characteristics on structural behaviour can be analysed objectively. FEM simulations were performed with static loading representing vehicle operating conditions, while aluminium was modelled as isotropic and composite as orthotropic to capture its anisotropic properties. The analysis results show that filament winding composite chassis tend to have more controlled deformation and higher safety factors than 6061 aluminium alloy, although the stress distribution in composites shows sensitivity to fibre configuration and profile thickness. These findings indicate that fibre orientation plays an important role in directing structural stiffness and load distribution in composite chassis. However, the interpretation of stress results and safety factors in composites needs to be done carefully because the Von Mises criteria have limitations in representing anisotropic material failure. The main contribution of this research lies in presenting a controlled structural comparison between metal and filament winding composite materials, as well as confirming the potential and limitations of composites as materials for electric vehicle chassis.